Analysis Determining Liquidity, Growth, and Market Conditions in Increasing Company Value - Rizky Anang Saleh; Andi Surya; Desmon Desmon; M Nasir; Megasari Megasari; Armalia Reny WA; M Renandi Ekatama Surya (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effects of liquidity, firm growth, and market conditions on firm value in consumer noncyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period.Methodology: This study uses a quantitative research method with multiple linear regression analysis conducted using SPSS. The population consists of 124 consumer non-cyclicals companies for five years (620 data points). A purposive sampling technique resulted in 19 companies being observed for five years, with a total of 95 research samples. Data were collected through the documentation of annual financial reports.Results: The findings reveal that liquidity, as measured by the Current Ratio (CR), has a positive but insignificant effect on firm value (Tobin’s Q). Firm growth (GROWTH) and market conditions, as measured by the Price Earnings Ratio (PER), have positive and significant effects on firm value. Simultaneously, liquidity, firm growth, and market conditions have a positive and significant effect on firm value.Conclusions: The study concludes that firm growth and market conditions are the most influential factors in improving Firm Value (Tobin’s Q) for consumer non-cyclic companies in Indonesia.Limitations: This study is limited to consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period, and the variables tested are restricted to liquidity, growth, and market conditions.Contributions: This study contributes to the financial management literature by providing empirical evidence on the determinants of firm value and highlighting the role of firm growth and market conditions in enhancing firm value in the consumer non-cyclicals sector.